Strategi Komunikasi Pemasaran Perguruan Tinggi Swasta di Masa Pandemi COVID-19 - Herman; Wulan Muhariani (MUKASI: Jurnal Ilmu Komunikasi, 2022)
The spread of covid 19 since March 2020 has been evenly distributed throughout Indonesia, and has an impact on the joints of life, especially in the field of education. The decline in interest in higher education has decreased due to limited face-to-face meetings and a reduction in manpower in various fields, so that people choose to postpone college. Through case studies with interviews and literature, answering questions on the strategy of universities to find students during the pandemic, by elaborating on marketing communication, product strategies, pricing strategies, brands of goods that are explained with theories related to the answer to the decline that occurred due to the spread of COVID-19, reduction of labor in various fields. , as well as the shift in learning methods from alluring to daring to the stuttering of the community to adapt, so they choose to postpone college. The awareness, inquire, visit, & info session, apply, and admit strategies and their descriptions are alternatives to attracting new students, so that the impact of COVID-19 in the world of education can be minimized.